Peranan Jabatan Agama Islam Pahang (JAIP) dalam Penanganan Tindakan Lesbian, Gay, Bisexual, Transgender (LGBT) dan Hubungannya dengan Aqidah Islamiyah (Studi Kasus di Kota Raya Kuantan Pahang Darul Makmur, Malaysia) - Azera, Nur Shahidatul; Adenan, Adenan; Is, Fadhilah (Asian Journal of Islamic Studies and Da'wah, 2024)
LGBT social phenomena harm society's culture and have numerous detrimental effects, particularly on moral and ethical standards. It is true that issues pertaining to this societal phenomenon have existed from the time of Prophet Lut a.s. Allah Swt. annihilated them in a horrific earthquake. This study's objective is to examine how Jabatan Agama Islam Pahang (JAIP) responds to LGBT incidents and how it relates to Aqidah Islamiyah (Case Study in Kota Raya Kuantan Pahang Darul Makmur, Malaysia). Researchers used observations and interviews to gather data for this study. Because of this, the researcher moved straight to the research and conducted an interview with the deputy position selected as the source a place to observe and gather reliable and factual information, both in the form of primary and secondary data. When it comes to attempts to predict the formation of different social problems in society, JAIP is crucial. The research findings indicate that the publication of Sharia education and counseling modules, along with the implementation of rehabilitation programs for people concerned with signs of moral and cultural decline, play a role for Islamic religious perspectives in the idea of aqidah.